Improved Conceptual Understanding in Learning Biology through Local-ized and Contextualized Learning Activities - Montero, Jomel C.; Geducos, Dorie T. (Future Science / FSH-PH Publications, 2022)
Nowadays, a relatively large number of high school students have poor learning performance in Science which affects their academic performance and even the school National Achievement Test (NAT) result. This study determined the effectiveness of the localized and contextualized learning activities in improving the conceptual understanding of tenth-grade students in learning Biology for the Third Quarter of the School Year 2019-2020. The study was conducted using the pretest-posttest quasi-experimental design involving sixty (60) student-participants in a public secondary school in the Division of Surigao del Sur, Mindanao, Philippines. This study employed an intact group sampling technique in selecting the participants into two groups, the control group (conventional learning material/learning activity sheets) and the treatment group (localized and contextualized learning activities). The findings of the study revealed that the post-test mean score of the treatment group is greater than the post-test result of the control group. Also, there was a significant difference in the conceptual understanding of the students in the control group and treatment group. It shows that localized and contextualized learning activities promote a better understanding of the lesson. Hence, future study is suggested to develop and produce localized and contextualized instructional materials such as modules and worksheets for other learning competencies in Science.